PENGARUH IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR SERTA DAMPAKNYA PADA KINERJA PEGAWAI IKIP PGRI PONTIANAK - B2041142005, ERNI PARAMITA (Equator Journal of Management and Entrepreneurship (EJME), 2018)
The Research conducted on IKIP PGRI Pontianak was related to the influence of organizational environment towards organizational citizenship behavior and its effect on employees working performance. Performance was the most significant factor to be possess by human resources of certain organization. Human resources was said to be one of the most significant factor since the activities of an organization will not proceed smoothly without human resources who have competence and dedication towards organization. The aims of this research are to examine and analyze the influence of organizational environment towards organizational citizenship behavior and its effect on employees working performance in IKIP PGRI Pontianak. The form of this research is causal comparative. The primary data were collected through questionnaires and interviews, while the secondary data were the data sourced from IKIP PGRI Pontianak. The sample were random sample. They were the employees of IKIP PGRI Pontianak IKIP PGRI Pontianak as much as 79 people.The results show that organizational environment has a positive significant influence towards organizational citizenship behavior of employees of IKIP PGRI Pontianak. In addition, organizational environment also has a positive significant influence towards employees working performance in IKIP PGRI Pontianak..Â Keywords : Organization